Alkynes as a versatile platform for construction of chemical molecular complexity and realization of molecular 3D printing. (4th April 2016) - Galkin, K I; Ananikov, V P
Abstract: The current level of scientific and technological development requires the formation of general tools and techniques. One of the most versatile technologies is 3D printing, which allows fast and efficient creation of materials and biological objects of desired shape and composition. Today, methods have been developed for 3D printing of macro- and nano-sized objects and for production of films and deposited materials with molecular precision but the most promising technology is printing at the molecular level (molecular 3D printing) for the purpose of direct construction of molecular complexity. This process is currently at the initial stage concerning selection of simple molecules to be used as building blocks possessing flexibility, availability and ease of modification. In this review, we examine the possible versatile synthons suitable for preparation of the main types of organic compounds using molecular 3D printing. The surveyed data strongly indicate that alkyne molecules may be used as a building material in a molecular 3D printer working on hydrocarbons. The bibliography includes 428 references.